THE IMPACT OF ACOUSTICS ON THE DESIGN OF A VIBRANT CULTURAL CENTRE IN YENAGOA, BAYELSA STATE. - Okoro , Ngozi A; Adeyemi , Tolu O (International Journal of Civil Engineering and Architecture and Real Estate, 2024)
Cultural centres are venues or institutions dedicated to promoting and preserving the culture of a particular region, community or group of people. In this present era where almost everyone and everything is nearly taken over by technology, the cultural identity of the nation is gradually perishing. Cultural centres offer a wide range of activities relating to the arts and traditions of the people they represent and play a crucial role in fostering the understanding and appreciation of cultural heritage and diversity. In many states where diverse ethnic groups exist, like Bayelsa State for example, Cultural centres serve as focal points for people of the different ethnic groups, both within and outside the state, to promote cross-cultural understanding and social interactions. Bayelsa State lies in the heart of the Niger Delta in the Southern part of Nigeria and it is a home of a variety of cultures that reflect the history, beliefs, values and traditions of the different ethnic groups in the State. The existence of Cultural centres is essential in order to safeguard the customs and traditions of the people. The influence of acoustics in moulding the tourist experience is an aspect that is often overlooked or neglected in the design of these cultural centres. This research addresses the significance of acoustics in various spaces within the cultural centre, from performance halls and exhibition areas to communal gathering spaces. It explores the effective application of acoustic principles within the facility to create an immersive and engaging environment for the people and discusses how the design of the spaces in the facility, materials used for the construction, soundproofing techniques and acoustic treatments can enhance the quality of auditory experiences. Through qualitative and quantitative research methods, such as case studies and survey, the study explores several acoustics inclined construction materials and how it is integrated in the design of. Cultural Centre. Since technology has been constantly evolving and improving with time, new techniques of utilising it as a tool for improving architectural acoustics have begun to emerge. The effective application of acoustics in cultural centres serves to create a sound ambience where cultural expressions are celebrated, and the rich tapestry of traditions is woven into the fabric of the experience of all who visit.